(untitled) (The Peerian Journal, 2025)
Deletion is a general linguistic phenomenon shared by all languages, especially Arabic. Deletion is an established phenomenon that cannot be dispensed with, and grammarians and rhetoricians have studied and analyzed this phenomenon. Deletion is the omission of one or more words from a sentence to achieve rhetorical purposes. Deletion requires a verbal or situational clue indicating the deleted element. The research addressed the most important reasons for deleting the verb, which are frequent use, the addressee’s knowledge of the deleted word, and brevity and abbreviation. The research addressed the types of deletion of the verb, and the verb is divided according to the appearance of the deleted verb into two sections: the first: deleting the verb as permissible, and the second: deleting the verb as obligatory. Deletion sometimes aims to stimulate the imagination of the reader or listener by estimating the deleted element. The places where the verb is deleted in the interpretation of Al-Lubab varied. The research dealt with the places where the verb is deleted due to preoccupation, the deletion of the source factor or the absolute object, the deletion of the verb in specialization, the deletion of the verb in the oath, the deletion of the verb in the condition, the deletion of “kana” with its subject and keeping its predicate, the deletion of the verb on the condition of interpretation, and the deletion of the verb in temptation